Development of a Visual Novel Game on Evolution Material - Taufik Ramdani, Ahmad; Suhada, Idad; Sholikha, Mar'atus (KnE Social Sciences, 2024)
Technological developments are closely related to improving the quality of education. Currently, games are widely used as learning media. One of these games is visual novel games. This study aimed to determine the characteristics of the visual novel game learning media, the level of student learning outcomes, and student responses. The research method used is Research and Development using a 3-D model. The characteristics of the website-based visual novel game learning media were developed using visual novel maker software to produce media products that match the specifications of the learning media. The results of the validation test were 85.33% of the material expert validation assessment (very feasible), the media expert validation assessment 76% (very feasible), the media and material validation assessment from the biology subject teacher 71.34% (adequate), and the media readability validation assessment from students was 76.9%. The average value of validation obtained from the four validators was 77.39% (very feasible). The level of student learning outcomes after using learning media can be known by doing a pretest and post-test, the results obtained in the form of a normalized gain calculation value (N-Gain) of 0.56 and these results include moderate criteria. Finally, the average value of student responses obtained was 74.24% including the positive category. Based on the data from the analysis of the research, it shows that website-based visual novel game learning media can improve student learning outcomes. Keywords: visual novel game, evolution, material